Stabilization of the ADP/metaphosphate intermediate during ATP hydrolysis in pre-power stroke myosin: quantitative anatomy of an enzyme - Kiani, Farooq Ahmad; Fischer, Stefan (JBC papers in press, 2013)
It has been proposed recently that ATP hydrolysis in ATPase enzymes proceeds via an initial intermediate in which the dissociated γ-phosphate of ATP is bound in the protein as a metaphosphate (PγO3−). A combined quantum/classical analysis of this dissociated nucleotide state inside myosin provides a quantitative understanding of how the enzyme stabilizes this unusual metaphosphate. Indeed, in vacuum, the energy of the ADP3−·PγO3−·Mg2+ complex is much higher than that of the undissociated ATP4−. The protein brings it to a surprisingly low value. Energy decomposition reveals how much each interaction in the protein stabilizes the metaphosphate state; backbone peptides of the P-loop contribute 50% of the stabilization energy, and the side chain of Lys-185+ contributes 25%. This can be explained by the fact that these groups make strong favorable interactions with the α- and β-phosphates, thus favoring the charge distribution of the metaphosphate state over that of the ATP state. Further stabilization (16%) is achieved by a hydrogen bond between the backbone C=O of Ser-237 (on loop Switch-1) and a water molecule perfectly positioned to attack the PγO3− in the subsequent hydrolysis step. The planar and singly negative PγO3− is a much better target for the subsequent nucleophilic attack by a negatively charged OH− than the tetrahedral and doubly negative PγO42− group of ATP. Therefore, we argue that the present mechanism of metaphosphate stabilization is common to the large family of nucleotide-hydrolyzing enzymes. Methodologically, this work presents a computational approach that allows us to obtain a truly quantitative conception of enzymatic strategy.
Gesehen am 07.04.2021